Investigating the Impact of Functional Electrical Stimulation (FES) on Motor Recovery and Secondary Complications: A Qualitative Study of Spinal Cord Injury Patients’ Experiences - Shumaila Khan; Saira Muzaffar Shah; Hoor Bakht; Muhammad Rehman; Mahila Abbas; Ayesha (Dialogue Social Science Review (DSSR), 2025)
Background: Spinal cord injury (SCI) has a considerable impact on motor function, which induces secondary complications and reduces the patient’s independence and quality of life. Functional Electrical Stimulation (FES) has been developed as a therapeutic approach to regain motor function by activating paralyzed muscles. Nonetheless, there is limited research investigating patient experiences and perceived effectiveness of FES. Objective: To investigate the clinical, functional, and psychosocial effects of FES on motor functional recovery and on the presentation of secondary complications in SCI patients based on their experiences and perceived benefits and challenges of treatment. Method: This qualitative study included semi-structured interviews with 15 SCI patients undergoing FES therapy. Data were analyzed thematically using NVivo software to capture major themes around motor recovery, secondary complications, and patient perspectives. Results: Participants reported differing levels of motor improvement, whether through increased mobility and muscle strength, or slow or inconsistent progress. Symptoms like soreness and fatigue were occasionally mentioned as side effects but were perceived by most as temporary challenges. Adherence to therapy was notably influenced by psychological resilience and motivation. Access to FES was highlighted as a significant challenge due to costs and availability within the public healthcare setting. Conclusion: Functional electrical stimulation (FES) therapy improves motor function in patients with spinal cord injury (SCI) by activating peripheral nerves. However, the impact of this therapy on motor recovery remains unclear. Overcoming accessibility barriers and ensuring ongoing support for rehabilitation can improve patient outcomes.” This approach requires further research into optimizing FES interventions for long-terms recovery.